Associations between fentanyl use and initiation, persistence, and retention on medications for opioid use disorder among people living with uncontrolled HIV disease. (1st November 2021) - Cook, Ryan R.; Torralva, Randy; King, Caroline; Lum, Paula J.; Tookes, Hansel; Foot, Canyon; Vergara-Rodriguez, Pamela; Rodriguez, Allan; Fanucchi, Laura; Lucas, Gregory M.; Waddell, Elizabeth N.; Korthuis, P. Todd
Abstract: Background: Associations between fentanyl use and initiation and retention on medications for opioid use disorder (MOUD) are poorly understood. Methods: Data were from a multisite clinical trial comparing extended-release naltrexone (XR-NTX) with treatment as usual (TAU; buprenorphine or methadone) to achieve HIV viral suppression among people with OUD and uncontrolled HIV disease. The exposure of interest was fentanyl use, as measured by urine drug screening. Outcomes were time to MOUD initiation, defined as date of first injection of XR-NTX, buprenorphine prescription, or methadone administration; MOUD persistence, the total number of injections, prescriptions, or administrations received over 24 weeks; and MOUD retention, having an injection, prescription, or administration during weeks 20–24. Results: Participants (N = 111) averaged 47 years old and 62% were male. Just over half (57%) were Black and 13% were Hispanic. Sixty-four percent of participants tested positive for fentanyl at baseline. Participants with baseline fentanyl positivity were 11 times less likely to initiate XR-NTX than those negative for fentanyl (aHR = 0.09, 95% CI 0.03–0.24, p < .001), but there was no evidence that fentanyl use impacted the likelihood of TAU initiation (aHR = 1.50, 0.67–3.36, p = .323). Baseline fentanyl use was not associated with persistence or retention on any MOUD. Conclusions: Fentanyl use was a substantial barrier to XR-NTX initiation for the treatment of OUD in persons with uncontrolled HIV infection. There was no evidence that fentanyl use impacted partial/full agonist initiation and, once initiated, retention on any MOUD. Highlight: Fentanyl use decreases extended-release naltrexone initiation. Fentanyl use may not affect buprenorphine or methadone initiation. Fentanyl use may not affect retention on medication for opioid use disorder.